PROFESIONALITAS DAN PERSONALITAS GURU KRISTEN: PENGEMBANGAN SUMBER DAYA MANUSIA BERKARAKTER DAN KOMPETEN MENUJU INDONESIA UNGGUL - Nurasyah Dewi Napitupulu (Sekolah Tinggi Teologia Wesley Methodist Indonesia, 2020)
Many studies assume that the professionalism of teachers is influenced by his personality. Personality is a psychological characteristic that contributes to learning outcomes and academic achievement. However, research that proves this assumption is limited in the domain of Christian teachers as part of teachers inIndonesia. This study aims to analyze the correlation between teachers’ personality and professionalism obtained through questionnaires and interviews. The analysis was carried out on 16 Christian teachers participated who were attending the Postgraduate Program in